Design of Automatic Fan Base On Arduino Uno Microcontroler And DHT11 Sensor - Muhammad Sakban Batubara; Purnama Helena Hutabarat (Universitas Islam Kuantan Singingi, 2025)
The temperature of the human body can fluctuate depending on environmental conditions, particularly the surrounding room temperature. To maintain comfort, a cooling device capable of providing adequate airflow is required, and one commonly used solution is an electric fan. This study focuses on designing and implementing an automatic fan system controlled by an Arduino Uno microcontroller and a DHT11 temperature sensor. The system is programmed to activate the fan automatically when the detected room temperature exceeds a predetermined threshold. In the design phase, the Arduino Uno functions as the core controller due to its ability to process sensor input and manage hardware operations efficiently. The DHT11 sensor measures both temperature and humidity, transmitting the data to the microcontroller, which then delivers a control signal to the relay module. Following the design stage, system implementation is carried out using the C++ programming language through the Arduino IDE. The program continuously reads temperature values from the DHT11 sensor, enabling real-time decision-making. When the temperature reaches the specified limit, the microcontroller triggers the relay, causing the fan to operate automatically. The results of this study show that the fan responds accurately to temperature changes, providing a practical automatic cooling solution.